2013
DOI: 10.1093/toxsci/kft167
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Impedance Assays for Predictive Preclinical Drug Screening of Kinase Inhibitor Cardiovascular Toxicity

Abstract: Cardiovascular (CV) toxicity is a leading contributor to drug attrition. Implementing earlier testing has successfully reduced human Ether-à-go-go-Related Gene-related arrhythmias. How- ever, analogous assays targeting functional CV effects remain elusive. Demand to address this gap is particularly acute for kinase inhibitors (KIs) that suffer frequent CV toxicity. The drug class also presents some particularly challenging requirements for assessing functional CV toxicity. Specifically, an assay must sense a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…For example, functional cardiotoxicity of microtubule-affinity regulating kinase (MARK) inhibitors, which initially presented with reduced blood pressure in dogs (see patent [35]), could be recapitulated in vitro as beat inhibition without cytotoxicity. Several lines of data indicate that MARK SMKI cardiotoxicity is on-target-relative potency for MARK inhibition aligned with potency of beat inhibition, genetic knockdown of MARKs decreased beat amplitude, as did targeting the pathway with microtubule inhibitors ( [19] ; Fig. 6).…”
Section: Detecting Kinase Inhibitor Cardiotoxicitymentioning
confidence: 88%
See 3 more Smart Citations
“…For example, functional cardiotoxicity of microtubule-affinity regulating kinase (MARK) inhibitors, which initially presented with reduced blood pressure in dogs (see patent [35]), could be recapitulated in vitro as beat inhibition without cytotoxicity. Several lines of data indicate that MARK SMKI cardiotoxicity is on-target-relative potency for MARK inhibition aligned with potency of beat inhibition, genetic knockdown of MARKs decreased beat amplitude, as did targeting the pathway with microtubule inhibitors ( [19] ; Fig. 6).…”
Section: Detecting Kinase Inhibitor Cardiotoxicitymentioning
confidence: 88%
“…Chk inhibitors that presented in clinical trials with heart rate irregularities could be replicated in vitro as beat inhibition without cytotoxicity. However, neither pharmacology nor genetic inhibition indicated that these effects were Chk-mediated, thereby suggesting off-target contribution(s) and offering an assay to explore safer compounds [19].…”
Section: Detecting Kinase Inhibitor Cardiotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The zebrafish has contributed to obtain measurements as action potential trough voltage mapping, to determine cells coupling [20] , and this fact together with calcium signaling, are important for cardiomyocyte proliferation and differentiation [21] . The last decade's large animals, such as mice, rats and rabbits, have been widely used to study cardiotoxicity after drug administration [22][23][24] , presenting some limitations. For instance, rodents can be insensitive to compounds' cardiotoxicity, particularly when the endpoint measurement is left ventricular contractile function [25] .…”
Section: Zebrafish As Cardiotoxicological Toolmentioning
confidence: 99%